Sustainability science managing risk and resilience for sustainable development - Becker, Per (Amsterdam Elsevier, 2024)
Sustainability is increasingly important across functional sectors and scientific disciplines. Policy-makers, practitioners, and academics continue to wrestle with the complexity of risk, resilience, and sustainability, but because of the necessary transdisciplinary focus, it is difficult to find authoritative content in a single source. Sustainability Science: Managing Risk and Resilience for Sustainable Development, Second Edition, contributes to filling that gap and is completely revised with several new chapters. It asserts that all efforts for the sustainability of humankind are undermined by the four fundamental challenges of complexity, uncertainty, ambiguity, and dynamic change. While there are no silver bullets, this book contends that we need systems approaches, risk approaches, participatory approaches, and resilience approaches to address each of them and endeavours to provide such. With that in mind, this book describes the state of the world (Part I), proposes a way to approach the world (Part II), and suggests how to set out to change the world (Part III).
Includes bibliographical references and index.
Keywords: Sustainable development